2022
DOI: 10.1021/acs.jmedchem.2c01768
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Effect of Halogenation in a Series of Potent and Selective A2B Adenosine Receptor Antagonists

Abstract: The modulation of the A2B adenosine receptor is a promising strategy in cancer (immuno) therapy, with A2BAR antagonists emerging as immune checkpoint inhibitors. Herein, we report a systematic assessment of the impact of (di- and mono-)halogenation at positions 7 and/or 8 on both A2BAR affinity and pharmacokinetic properties of a collection of A2BAR antagonists and its study with structure-based free energy perturbation simulations. Monohalogenation at position 8 produced potent A2BAR ligands irrespective of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…The study also demonstrated a marked effect on immune system cells, recovering from adenosine-mediated immunosuppression and increasing the production of proinflammatory cytokines. This effect in the immune system has been recently verified [ 138 ].…”
Section: Anticancer Compounds Obtained From Mcrs Approachesmentioning
confidence: 75%
See 1 more Smart Citation
“…The study also demonstrated a marked effect on immune system cells, recovering from adenosine-mediated immunosuppression and increasing the production of proinflammatory cytokines. This effect in the immune system has been recently verified [ 138 ].…”
Section: Anticancer Compounds Obtained From Mcrs Approachesmentioning
confidence: 75%
“…With the initiative to develop novel cancer immunotherapeutic agents via the modulation of the A 2B adenosine receptor, Sotelo et al [ 134 , 135 , 136 , 137 , 138 ] discovered several families of (monocyclic, bicyclic or tricyclic) pyrimidine derivatives ( Scheme 16 ) that were readily and efficiently assembled through a three-component Biginelli reaction.…”
Section: Anticancer Compounds Obtained From Mcrs Approachesmentioning
confidence: 99%
“…[327] The subsequent modification of the structures of pyrimidobenzimidazoles was associated with the replacement of Me groups by CF 3 , [328] the bioisosteric substitution of the heterocycle at the C-4 atom, [329] and the introduction of halogen atoms into the benzimidazole fragment. [330] To establish the relationship between the stereochemical structure and the ability to bind to A 2B ARs, four single diastereomers and two diastereomeric pairs of pyrimidobenzimidazole with a CF 3 substituent in the ester group were obtained (Figure 9). [328] The most active were (3R,4S)-278 c and (3S,4S)-279 c isomers.…”
Section: Metabolic Disorders Controlmentioning
confidence: 99%
“… [9] Halogenation of drug candidates can increase membrane permeability, [10] enhance blood‐brain barrier transport, [11] and strengthen the binding interactions between a ligand and its target, thereby increasing the ligand potency. [ 9 , 12 ] The halogenation of the indole ring in particular has been proven to tune some properties of multiple cancer drug leads isolated from marine environments. [13] Furthermore, halogenated indoles serve as versatile precursors for the synthesis of more complex structures, as they facilitate cross‐coupling reactions and other synthetic transformations.…”
Section: Introductionmentioning
confidence: 99%
“…In such drug discovery processes, halogenation is commonly used as a means to improve the properties of a lead drug candidate, [8] and consequently, the presence of halogens is frequent in drugs, with approximately 25 % of all commercialized pharmaceuticals containing a halogen atom in their structure [9] . Halogenation of drug candidates can increase membrane permeability, [10] enhance blood‐brain barrier transport, [11] and strengthen the binding interactions between a ligand and its target, thereby increasing the ligand potency [9,12] . The halogenation of the indole ring in particular has been proven to tune some properties of multiple cancer drug leads isolated from marine environments [13] .…”
Section: Introductionmentioning
confidence: 99%